Argyreia sharadchandrajii (Convolvulaceae), a new species from the Western Ghats, India - Lawand, P. R.; Shimpale, V. B. (Rheedea, 2026)
Argyreia sharadchandrajii Lawand & Shimpale, a new species from the Western Ghats of Maharashtra, India is described and illustrated. Argyreia sharadchandrajii is morphologically similar to A. pilosa Wight & Arn. but differs in habit, shape of leaves and bracts, indumentum and size of peduncle, sepal and berries. Notes on taxonomy and conservation status are provided.